Correlação entre cor da coroa dentária e a saturação de oxigênio em dentes submetidos a procedimentos clareadores - Carvalho, Igor César Ribeiro de (2021)
Objective: To evaluate the correlation between the color of the dental crown and the result of the pulse oximeter in healthy teeth before and after bleaching procedures. Materials and methods: According to the sample calculation, it would be possible with 62 teeth to detect as statistically significant correlation coefficients between the color of the dental crown and the result of the pulse oximeter, with moderate magnitude (r = 0.40) considering a power of 90%. This is a clinical trial with a sample consisting of 70 participants. The color of the dental crown of 70 healthy upper central incisors was assessed using a spectrophotometer and the oxygen saturation level of the pulp was recorded using a pulse oximeter. Both measurements were made before and 30 days after the completion of the bleaching procedures. The bleaching was performed by the combined technique, with the application of the 35% hydrogen peroxide whitening gel, in the office stage, and with 10% carbamide peroxide, in the home stage, for 16 days. The influence of each coordinate on the color difference of the dental crown was analyzed according to ABNT (2004). The symmetry of the variables was verified by the Kolmogorov Smirnov test, and the quantitative variables were described by means and standard deviations. The correlation between quantitative variables was established using Pearson's correlation coefficient. The level of significance considered was 5%. Results: A statistically significant change was observed between values recorded by the pulse oximeter before (85.0% ± 4.1) and after 30 days after the completion of the bleaching procedures (86.4% ± 2.3), as well as between the values of the color coordinates initially detected (L * = 89.0 ± 2.8; a * = -1.7 ± 0.7; b * = 20.7 ± 3.2) and 30 days after the tooth whitening (L * = 91.2 ± 2.6; a * = - 3.0 ± 0.6; b * = 13.5 ± 2.5). 30 days after the completion of the bleaching procedures, the dental crowns were clearer with a difference between L * s equal to 1.4, more greenish with a difference between a * s equal to 1.3, and more bluish, with a difference between b * s equal -7.2. There was no correlation between the values of the coordinates L *, a * and b * and the results recorded by the pulse oximeter in the initial period, r = -0.22, r = 0.02, r = 0.11, respectively, nor after 30 days after the completion of the bleaching procedures, r = -0.20, r = 0.01, and r = -0.12, respectively. Conclusion: Changes in the pulse oximeter records do not correlate with the color change of the dental crown promoted by bleaching procedures.